The Art of George Ames Aldrich - Greenhouse, Wendy, 1955- (Book collections on Project MUSE., 2013)
A highly regarded impressionist-style artist, George Ames Aldrich drew on his years of experience living and studying in Europe to create beautiful landscape paintings. His life and work are explored in this book. Many of the artist's finest creations, some representing French subjects and others depicting the midwestern steel industry and American landscapes, are included in this book. It features color reproductions, along with other archival and contextual images. Essays by Michael Wright and Wendy Greenhouse explore in detail Aldrich's life, influences, sources of inspiration, and the historical context of the art.